2018
DOI: 10.14254/1800-5845/2018.14-4.7
|View full text |Cite
|
Sign up to set email alerts
|

Employees Management: Evidence from Gamification Techniques

Abstract: The purpose of this paper is to find out the effect of Gamification on employee motivation, employee engagement, employee retention, employee loyalty and organizational commitment. We want to know this in order to check the viability of Gamification strategy for business development in Pakistan. Participants were 142 University students, who were working as well, we divided them into two groups, control group and Gamified group, we gave both groups pretest and post-test questionnaire. ANOVA and t-test were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
(46 reference statements)
0
8
0
1
Order By: Relevance
“…Since we can not affirm that gamification generates consensus on whether it is a viable or adaptable tool to all markets and sectors (Hamari et al 2014;Hussain et al 2018), understanding how users view themselves is crucial to measure the possible success of a gamified initiative.…”
Section: Attitude Towards the Use Of A Gamified Applicationmentioning
confidence: 97%
“…Since we can not affirm that gamification generates consensus on whether it is a viable or adaptable tool to all markets and sectors (Hamari et al 2014;Hussain et al 2018), understanding how users view themselves is crucial to measure the possible success of a gamified initiative.…”
Section: Attitude Towards the Use Of A Gamified Applicationmentioning
confidence: 97%
“…Lastly, there are a few standalone studies that examined the effectiveness of gamification in other areas. Hussain et al (2018) explored variables such as employee engagement and commitment in a study where the experimental group completed professional tasks in a “gamified environment with leaderboard scores, badges, giveaways, token [s] of appreciation, and achievement levels for each employee based on judges’ evaluation” (p. 101). They found that gamification positively influenced engagement, retention, and organizational commitment when compared to the control group.…”
Section: Gamification For Hrd: Emergent Research Themesmentioning
confidence: 99%
“…While gamification has been found to be effective in several HRD settings, insights are scattered and emerging. Multiple studies have shown that gamification supported desired outcomes such as employee learning (Brull et al, 2017), employee well-being (Dadaczynski et al, 2017), and employee engagement (*Hussain et al, 2018; *Silva et al, 2019). Similarly, several studies have demonstrated that gamification reduced unwanted outcomes, such as eliminating non–value-adding tasks (Khanzadi et al, 2018) and reducing stress levels when embedded in a workplace wellness program (Lowensteyn et al, 2019).…”
mentioning
confidence: 99%
“…Pada era disruptif 4.0 ini banyak generasi berlombalomba dalam menciptakan sebuah inovasi baru, hal itu membuat pertumbuhan teknologi menjadi meningkat tajam salah satunya adalah gamifikasi. Gamifikasi sendiri mempunyai arti suatu konsep yang mempunyai lapisan fitur-fitur layaknya sebuah game yang terhubung atau terintegrasi dengan blockchain [1] Gamification [2], [3] Disebabkan kurangnya pemahaman seputar blockchain, tren ini baru menjadi populer di kalangan individu dan organisasi di dunia virtual selama beberapa tahun terakhir. Perusahaan menambahkan suatu ide pada bagian sistem informasi berupa fitur game [4], [5], web dan aplikasi [6], aplikasi IoT [7], [8] Gamifikasi semakin melebarkan sayapnya hal itu membuatnya semakin dikenal oleh para pemimpin, perusahaan, dan pengembang.…”
Section: Pendahuluanunclassified